Mitogen-Activated Protein Kinase p38 Controls the Expression and Posttranslational Modification of Tristetraprolin, a Regulator of Tumor Necrosis Factor Alpha mRNA Stability - Mahtani, Kamal R. (American Society for Microbiology, 2001)
Signal transduction pathways regulate gene expression in part by modulating the stability of specific mRNAs. For example, the mitogen-activated protein kinase (MAPK) p38 pathway mediates stabilization of tumor necrosis factor alpha (TNF-α) mRNA in myeloid cells stimulated with bacterial lipopolysaccharide (LPS). The zinc finger protein tristetraprolin (TTP) is expressed in response to LPS and regulates the stability of TNF-α mRNA. We show that stimulation of RAW264.7 mouse macrophages with LPS induces the binding of TTP to the TNF-α 3′ untranslated region. The p38 pathway is required for the induction of TNF-α RNA-binding activity and for the expression of TTP protein and mRNA. Following stimulation with LPS, TTP is expressed in multiple, differentially phosphorylated forms. We present evidence that phosphorylation of TTP is mediated by the p38-regulated kinase MAPKAPK2 (MAPK-activated protein kinase 2). Our findings demonstrate a direct link between a specific signal transduction pathway and a specific RNA-binding protein, both of which are known to regulate TNF-α gene expression at a posttranscriptional level.